Impact of a Service Provider Incentive Payment Scheme on Quality of Reproductive and Child-health Services in Egypt (Journal of Health, Population and Nutrition, 2010)
A case-control, quasi-experimental study was designed (post-test only) to investigate the effect of a performance-based incentive payment scheme on behaviours of public-sector service providers in deliveringa basic package of maternal and child-health services in Egyptian primary healthcare units. The resultsshowed significant improvements in the quality of family-planning, antenatal care, and child-care servicesas reported by women seen in clinics where the incentive payment scheme was in operation as measuredby various indicators, including both technical and inter-personal communication content. An analysis ofcharacteristics of the service providers and clients found no significant or meaningful differences betweenthe study groups, and the facilities of both the study groups were essentially the same. Some findings aresuggestive of other influences on behaviours of the service providers not captured by the data-collectioninstruments of the study. Subsequent to this study, the payment scheme has been rolled out to other districtsin Egypt.Key words: Performance payments; Child Health; Reproductive health; Impact studies; Quality of care;Case-control studies; Health services; EgyptDOI: 10.3329/jhpn.v28i3.5556J HEALTH POPUL NUTR 2010 Jun;28(3):273-280